THE MODERN STATUS AND DEVELOPMENT’ TENDENCIES OF PSYCHOPHYSIOLOGY IN ARMENIA - Grigoryan , V. H.; Stepanyan , L. S. (Արդի հոգեբանություն, 2018)
The history of becoming and development of psychophysiology as a science in the world, particularly in the Armenian was shown in the article. Methodical bases, object and problems of psychophysiology was presented. The perspective of development and the investment' sphere of psychophysiological knowledge was found out.